ANALYSIS OF THE PROBLEM SITUATION AS A BASIS FOR THE TEACHING OF WRITING AS A SOCIAL PRACTICE (Neo Scientific Peer Reviewed Journal, 2024)
This article delves into the exploration of the problem situation analysis as a foundational element for the pedagogy of teaching writing as a social practice. Recognizing the pivotal role of context in effective language instruction, this study investigates how understanding and analyzing problem situations contribute to shaping the teaching of writing within a social framework. By emphasizing the socio-cultural and pragmatic dimensions of written expression, the research seeks to establish a comprehensive understanding of the interplay between context and writing pedagogy. The outcomes of this analysis hold significance for educators and practitioners engaged in language instruction, offering insights into optimizing teaching methodologies that align with the intricacies of real-world communicative situations. This abstract serves as a concise guide for those interested in enhancing the social relevance and efficacy of writing instruction.